Persistent DNA Double-Strand Breaks After Repeated Diagnostic CT Scans in Breast Epithelial Cells and Lymphocytes - Bogdanova, Natalia V.; Jguburia, Nina; Ramachandran, Dhanya; Nischik, Nora; Stemwedel, Katharina; Stamm, Georg; Werncke, Thomas; Wacker, Frank; Dörk, Thilo; Christiansen, Hans (Frontiers in Oncology, 2021)
DNA double-strand breaks (DSBs) induction and repair have been widely studied in radiation therapy (RT); however little is known about the impact of very low exposures from repeated computed tomography (CT) scans for the efficiency of repair. In our current study, DSB repair and kinetics were investigated in side-by-side comparison of RT treatment (2Gy) with repeated diagnostic CT scans (≤20 mGy) in human breast epithelial cell lines and lymphoblastoid cells, harboring different mutations in known DNA damage repair proteins. Immunocytochemical analysis of well known DSB markers γH2AX and 53BP1, within 48h after each treatment, revealed highly correlated numbers of foci, similar appearance/disappearance profiles. The levels of γH2AX and 53BP1 foci after CT scans were up to 30-60% of those occurring after 2Gy irradiation. The DNA damage repair after diagnostic CT scans was monitored and quantitatively assessed by both, γH2AX and 53BP1 foci, in different cell types. Subsequent diagnostic CT scans in 6 and/or 12 weeks intervals resulted in elevated background levels of repair foci which persisted up to 6 month. This “memory effect” was further enhanced in cells that were prone to genomic instability due to mutations in known regulators of DNA damage response (DDR) and may reflect a radiation-induced adaptive response of cells after low-dose x-ray exposure.